What's wrong with the coastal waters of Spelman Strait, Indonesia: Sustainable reef fisheries management is required - Rahmat Kurnia; Muis; Agus Alim Hakim (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Reef fish in Spelman strait, Indonesia, is one of the fishery resources of considerable economic value. Unfortunately, there is still the use of unfriendly resources equipment (destructive fishing) that cause potential social problems. In this study, all components of the EAFM (Ecosystem Approach to Fisheries Management) composed of 6 domains, namely (1) fish stocks, (2) environment and ecosystem, (3) fishing techniques, (4) culture, (5) social, and (6) institutional are analyzed combining with MDS (Multidimensional Scaling). The main aim of this research is to find out the root solution for managing coral reefs in the coastal waters of Spelman Strait. The sustainability status review in the fishery resource domain, the environment and ecosystem domain, the fishery technique domain, the social domain, and the economic domain were respectively were 87.69, 88.17, 51.22, 51.61, and 72.67 which were in the category sustainable. Meanwhile, the sustainability status review in the institutional domain was 42.15, which was in the category of less sustainable. Institutions are the primary base for reef fishery protection in the Spelman Strait.